2008
DOI: 10.1016/j.juro.2007.08.147
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Comparison of Retroperitoneoscopic Versus Open Adrenalectomy for Pheochromocytoma

Abstract: Compared with open surgery retroperitoneoscopic lateral adrenalectomy for pheochromocytoma is a safe, minimally invasive and effective procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 18 publications
2
39
0
1
Order By: Relevance
“…Guiding this practice is the fact that tumor manipulation has been shown to be the most significant intraoperative stimulus for catecholamine release during both open and laparoscopic resections. 27,30 Limiting tumor manipulation and applying pharmacological vasodilation when hypertension is persistent has resulted in no cardiovascular morbidity or mortality in our series. The sole exception was one patient who developed a severe pulmonary embolus and died after being hospitalized for a month.…”
Section: 21mentioning
confidence: 84%
“…Guiding this practice is the fact that tumor manipulation has been shown to be the most significant intraoperative stimulus for catecholamine release during both open and laparoscopic resections. 27,30 Limiting tumor manipulation and applying pharmacological vasodilation when hypertension is persistent has resulted in no cardiovascular morbidity or mortality in our series. The sole exception was one patient who developed a severe pulmonary embolus and died after being hospitalized for a month.…”
Section: 21mentioning
confidence: 84%
“…Several authors have compared open or laparoscopic approaches retrospectively and concluded that laparoscopic adrenalectomy is superior in terms of intraoperative blood loss, transfusion rates, patient morbidity, start of oral intake, analgesia requirements as well as hospital stay [16,17] . Although long operative time was frequently reported in the early experience with laparoscopic adrenalectomy [18] , currently, it is obvious that the procedure provides a statistically significant shorter operative time [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Although long operative time was frequently reported in the early experience with laparoscopic adrenalectomy [18] , currently, it is obvious that the procedure provides a statistically significant shorter operative time [16] . Moreover, laparoscopic adrenalectomy has been proved to be superior in both pediatric and morbidly obese patients [19,20] .…”
Section: Discussionmentioning
confidence: 99%
“…This initial experience has been followed by others using the same approach or, alternatively, the retroperitoneal approach with the patient in the prone or in the lateral decubitus position [6,7] and the transperitoneal approach with the patient supine [8]. Several reports have confirmed the safety and efficacy of these techniques, and minimally, invasive adrenalectomy is presently considered the treatment of choice for a variety of benign lesions, including lesions of the medulla [9,10].…”
Section: Introductionmentioning
confidence: 99%